Tales from the waterhole - Graham, Bob 1942- (Cambridge, Mass Candlewick Press, 2014)
During the dry season, Morris the crocodile and his animal friends enjoy playing in and near the water hole
Ages 5-9
Keywords: Crocodiles -- Fiction; Friendship -- Fiction; Savanna animals -- Fiction